The Cross-Sectional and Longitudinal Association Between Perceived Neighborhood Walkability Characteristics and Depressive Symptoms in Older Latinos: The "¡Caminemos!" Study. (April 2015) - Hernandez, Rosalba; Kershaw, Kiarri N.; Prohaska, Thomas R.; Wang, Pin-Chieh; Marquez, David X.; Sarkisian, Catherine A.
Objective: Evaluate the cross-sectional and longitudinal association between perceived walkability-related neighborhood characteristics (e.g., traffic safety) and depressive symptoms among community-dwelling older Latino adults.Method: We used baseline, 12-month, and 24-month in-person interview data collected from Latinos aged ≥60 years participating in an exercise intervention at 27 senior centers ( N = 570).Results: In cross-sectional analyses, lower perceived neighborhood crime, indicative of greater neighborhood walkability, was associated with a lower odds of elevated symptoms of depression (odds ratio [OR] = 0.90; 95% confidence interval [CI] = [0.82, 0.996]; p = .04) after adjusting for demographic characteristics, linguistic acculturation, and medical comorbidities. Associations between Neighborhood Environment Walkability scales and incident depressive symptoms at 12- and/or 24-months were not statistically significant, but the point estimate for crime safety was consistent with cross-sectional findings (OR = 0.83; 95% CI = [0.64, 1.07]; p = .16), suggesting a protective effect for lower perceived neighborhood crime.Discussion: Lower perceived neighborhood crime is associated with reduced presence of elevated symptoms of depression in older Latinos.